Opiates inhibit neurogenesis in the adult rat hippocampus - Eisch, Amelia J. (The National Academy of Sciences, 2000)
Recent work implicates regulation of neurogenesis as a form of plasticity in the adult rat hippocampus. Given the known effects of opiates such as morphine and heroin on hippocampal function, we examined opiate regulation of neurogenesis in this brain region. Chronic administration of morphine decreased neurogenesis by 42% in the adult rat hippocampal granule cell layer. A similar effect was seen in rats after chronic self-administration of heroin. Opiate regulation of neurogenesis was not mediated by changes in circulating levels of glucocorticoids, because similar effects were seen in rats that received adrenalectomy and corticosterone replacement. These findings suggest that opiate regulation of neurogenesis in the adult rat hippocampus may be one mechanism by which drug exposure influences hippocampal function.